Identification of a sex‐specific molecular marker in Salminus brasiliensis (Characiformes) based on SCAR marker. (5th July 2017) - De Rosa, L.; Cruz, V. P.; Serrano, E. A.; Mendes, N. J.; Wasko, A. P.; Senhorini, J. A.; Pardo, B. G.; Martínez, P.; Oliveira, C.; Foresti, F.
Summary: Salminus brasiliensis, a characin regionally named 'dourado' (meaning goldfish), is the biggest characid fish, this species is cited in a list of fishes that are vulnerable. The goal of the present work was to try to identify, through AFLP technique to convert them into single locus markers (SCARs), in order to improve the sex identification in S. brasiliensis . Between possible sex‐specific AFLP markers in this study, one male‐specific were isolated (Les1) and converted into a SCAR marker. Les1 marker was confirmed sex‐specific in all samples tested. A sex‐specific DNA marker applicable to fish would be very useful for elucidating sex determination mechanism in fish.